THE STATE FATE IN POLIBUSINESSES - Raharjo, Agus (Jurnal Dinamika Hukum, 2015)
There is a new tendency in overcoming the problems of the nation. It appears all the stake-holders in this (legislative and executive) have played their role well to cause a decreasing in public trust in them. The case of "daddy needs stock" as the equivalent of the blue-collar crime cases, "mama needs stock" is a cause celebre that dragged the country officials and embarrassing when it is seen from the side of ethics. The tendency means that they create a problem, then published it, and ends with the emergence of a hero who overcomes all problems........